Utility of left atrial strain imaging for the determination of diastolic dysfunction in patients with STEMI. (14th October 2021) - Ohtaroglu Tokdil, K; Ongen, Z; Ikitimur, B; Durmaz, E; Tokdil, H; Koca, D; Raimoglu, U; Incesu, G; Pirdal, B Z; Verdiyev, H; Gulfidan, A; Karpuz, H
Abstract: Introduction: Since echocardiographic parameters indicating increased left ventricular filling pressure were validated in patients with stable coronary artery disease and patients with acute coronary syndrome were excluded, the utility of these parameters in ACS patients is not clarified. Recent studies suggest that left atrial strain imaging is a reliable method for the assessment of left ventricular diastolic dysfunction. Purpose: In this study, we aimed to investigate the clinical utility of left atrial strain imaging for the detection of increased LVFP. Methods: We prospectively included patients diagnosed with ST-segment elevation myocardial infarction who were treated with primary percutaneous intervention (pPCI). Left ventricular end-diastolic pressure was measured following the procedure. Comprehensive echocardiographic evaluation was performed within 24 hours of pPCI. Patients with atrial fibrillation and severe valvular heart disease were excluded. Normal LV end-diastolic pressure was accepted as <18 mmHg. Results: 76 patients were enrolled. Patients were divided into two groups according to LVEDP value. Group 1 patients included patients with normal LVEDP (42 patients) and the rest of the patients included into group 2 (27 patients). Comorbidities including hypertension (p: 0.408), diabetes (p: 0.696) and dyslipidaemia (p: 0.336) were similar between groups. Anterior myocardial infarction was more prevalent in group 2 patients (p: 0.012). Troponin and pro-BNP values were significantly higher in group 2 patients (p: 0.001 and p: 0.03 respectively). Left ventricular ejection fraction and left ventricular global strain values were significantly lower in group 2 patients (p: 0.048 and p: 0.025 respectively). Table 1 represents the comparison of strain values between groups. Left atrial reservoir strain rates were lower in group 2 patients (p: 0.09). Correlation analyses revealed that there is a statistically significant relationship between left atrial strain values and LVEDP (p: 0.003 and r: 0.238). Conclusion: In conclusion, our study has demonstrated that left atrial strain imaging is a useful non-invasive method for the assessment of increased LVEDP in patients with STEMI. Funding Acknowledgement: Type of funding sources: None.